Government Regional Strategies in Tourism Development in the Nusa Tenggara Barat Province Post-Pandemic - Kurniati, P S; Amin, M SAl; Nisa, T K (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to explain the regional government strategies in developing tourism in the Province of Nusa Tenggara Barat post-Covid-19 pandemic, with a focus on tourism potential and flagship tourism destinations, identification of tourism problems, and regional government strategies to achieve successful post-Covid-19 pandemic tourism development. The research used descriptive analysis method. Data were collected through literature study. Data were obtained from secondary data through previous research, digital footprints based on the website of the Government of Nusa Tenggara Barat Province and other related agencies. The research concluded that the Province of Nusa Tenggara Barat is able to achieve successful tourism development through several strategies including the determination of flagship tourism destinations by building new tourism attractions and increasing the capacity of human resources to enhance the quality of tourism services such as access to information for improved tourism marketing. The impact is that tourists have increased and the economy of the people of NTB has grown. Furthermore, the research also revealed that the strategies implemented by the Regional Government of NTB post-Covid-19 pandemic are effective and successful in rebuilding tourism in the Province of Nusa Tenggara Barat.